2018
DOI: 10.1111/scd.12295
|View full text |Cite
|
Sign up to set email alerts
|

Orthopedic‐orthodontic treatment of the patient with Turner's syndrome: Review of the literature and case report

Abstract: An early diagnosis and appropriate orthopedic-orthodontic intervention allow to simplify the management of TS patients and provide satisfactory and stable results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 23 publications
2
22
0
Order By: Relevance
“…However, if the treatment has been commenced after all, it should be taken under consideration that GH replacement therapy affects mandibular growth more than it affects development of maxilla. Also, both the pattern as well as the degree of growth during GH therapy is difficult to predict and GH rarely affects maturation of teeth [2,46,47].…”
Section: Orthodontic Treatment In Children Affected By Disorders Assomentioning
confidence: 99%
“…However, if the treatment has been commenced after all, it should be taken under consideration that GH replacement therapy affects mandibular growth more than it affects development of maxilla. Also, both the pattern as well as the degree of growth during GH therapy is difficult to predict and GH rarely affects maturation of teeth [2,46,47].…”
Section: Orthodontic Treatment In Children Affected By Disorders Assomentioning
confidence: 99%
“…In general, there is underdevelopment of various facial structures, including flattened (increased) cranial base angle, bi‐maxillary retrusion, high‐arched narrow palate, micrognathia, and class II malocclusion (Ahiko, Baba, Tsuji, Horikawa, & Moriyama, ; Cazzolla et al, ; Svanberg, Norevall, Ekman, Wahlberg, & Bågesund, ). At least one study (Juloski et al, ) reported that GH treatment improved some of these structures.…”
Section: Craniofacial and Dentalmentioning
confidence: 99%
“…DiGeorge syndrome associated to Familial Mediterranean Fever (FMF) is a very rare condition and the literature does not report cases of this kind of patients that undergo to orthopedic‐orthodontic therapy. The treatment of these complex patients requires a multidisciplinary approach, associated to early diagnosis and intervention …”
Section: Discussionmentioning
confidence: 99%
“…The treatment of these complex patients requires a multidisciplinary approach, associated to early diagnosis and intervention. 28,29 It is clear that this kind of patient requires an accurate anamnesis, a well-timed intervention, a careful dental-periodontal evaluation, good oral health standards, and an appropriate management of the orthodontic strengths in order to reach positive and stable in time results.…”
Section: Discussionmentioning
confidence: 99%